9(t-4)+3t=6(2t+5)-10

Simple and best practice solution for 9(t-4)+3t=6(2t+5)-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(t-4)+3t=6(2t+5)-10 equation:


Simplifying
9(t + -4) + 3t = 6(2t + 5) + -10

Reorder the terms:
9(-4 + t) + 3t = 6(2t + 5) + -10
(-4 * 9 + t * 9) + 3t = 6(2t + 5) + -10
(-36 + 9t) + 3t = 6(2t + 5) + -10

Combine like terms: 9t + 3t = 12t
-36 + 12t = 6(2t + 5) + -10

Reorder the terms:
-36 + 12t = 6(5 + 2t) + -10
-36 + 12t = (5 * 6 + 2t * 6) + -10
-36 + 12t = (30 + 12t) + -10

Reorder the terms:
-36 + 12t = 30 + -10 + 12t

Combine like terms: 30 + -10 = 20
-36 + 12t = 20 + 12t

Add '-12t' to each side of the equation.
-36 + 12t + -12t = 20 + 12t + -12t

Combine like terms: 12t + -12t = 0
-36 + 0 = 20 + 12t + -12t
-36 = 20 + 12t + -12t

Combine like terms: 12t + -12t = 0
-36 = 20 + 0
-36 = 20

Solving
-36 = 20

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8x+7x=135 | | x*0.2=x-1000 | | y/16=-20 | | -15=2(y-3)-5y | | 15(5x-2/5)+32 | | 5/6x+4=7/10x | | 7/6z=1/14-11/15 | | e^4x+4e^2x-12=0 | | (5/13)x=35 | | 32x(x+5)=4800 | | m=0.4(20)+38 | | 30x(x+2)=3600 | | 4x^2-28x-32=0 | | 3.9q-4.3-3.3q=0.4q-3.3 | | 7x=27 | | 2x/3=32/6 | | 2x^3-7x^2-30x=0 | | I=(500)(0.13)(2) | | r(r+3)=70 | | 2(-2)+-2-4(-2)=x | | -(2/5)x=(4/15) | | 4k-(3+k)=(2k+3) | | (4/11)x=20 | | -22/5=6/5(t+1) | | x-8.1=-5.2 | | 29+4y-2=13y-9-3y | | a^2+-5a=-4 | | x-45=-24 | | -4x+5y=-41 | | r(r+11)=42 | | 7(8c-1)-8=54c+7 | | x-7.8=-6.8 |

Equations solver categories